Barriers Barriers to the Growth of Food and Beverage MSMEs in Surabaya: A Strategic Analysis of Production and Marketing Challenges - Siswati, Endang; Rasharenda, Abrorri; Putri, Chelli Sagita; Putri, Suci Rahmawati; P, Wisnu Nur Alif (The Eastasouth Management and Business, 2025)
The purpose of this study was to determine the factors that inhibit the growth of food and beverage MSMEs in Surabaya in terms of production and marketing. Using a qualitative descriptive approach. The informants in this study were 9 MSMEs in the city of Surabaya. Data collection was carried out using documentation and in-depth interviews with MSME actors, direct observation of activities, production and marketing, Data analysis was carried out using techniques (Miles & Huberman, 1994), the results of the study found that MSME obstacles in the production process include other capital that is still minimal can affect business development, the production process is still simple can have an impact on slow efficiency in the production process, fluctuating raw materials make it difficult for micro business actors to make production and price plans, and lack of managerial knowledge in the business. The obstacles led by micro food and beverage entrepreneurs in the product marketing function are that marketing is still limited to the environment around the business, lack of promotion and minimal product packaging that inhibits business growth. Digital marketing strategies on social media can be used as an effective promotional strategy at an affordable cost to expand market share. The results of the study resulted in: producing 2 groups of MSME levels, namely strong and weak survival groups. Strong MSMEs have the criteria of large turnover with a balanced ratio of the number of employees to their turnover, while weak MSMEs have the criteria of relatively large turnover but with an unbalanced ratio of the number of employees to their turnover.